Inflammatory Markers upon Admission as Predictors of Outcome in COVID-19 Patients - Budhi Antariksa; Erlina Burhan; Agus Dwi Susanto; Mohamad Fahmi Alatas; Feni Fitriani Taufik; Dewi Yennita Sari; Dicky Soehardiman; Andika Chandra Putra; Erlang Samoedro; Ibrahim Nur Insan Putra Darmawan; Hera Afidjati; Muhammad Alkaff; Rita Rogayah (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Coronavirus disease 2019 (COVID-19) may cause dysregulation of the immune system, leading to hyperinflammation. Inflammatory markers can be used to predict in-hospital mortality in COVID-19 patients. This research was aimed to investigate the association between the levels of various inflammatory markers and mortality in COVID-19 patients.Methods: This study was conducted at Persahabatan National Respiratory Referral Hospital, Indonesia. Blood tests were performed upon admission, measuring the C-reactive protein, PCT, leukocyte, differential counts, and platelet count. The outcome measured was the mortality of hospitalized COVID-19 patients. Statistical analysis methods included the Mann–Whitney U test, receiver operating characteristic (ROC) analysis, and area under the curve (AUC) test.Results: Total 110 patients were included, and the laboratory values were analyzed to compare survivors and non-survivors. The non-survivor group had significantly higher leukocyte count, lower lymphocyte count, higher CRP and PCT levels, higher neutrophil-to-lymphocyte ratio (NLR), higher platelet-to-lymphocyte ratio (PLR), and lower lymphocyte-to-CRP ratio. As predictors of mortality, AUC analysis revealed that PCT, CRP, NLR, and PLR had AUCs of 0.867, 0.82, 0.791, and 0.746, respectively.Conclusions: Routine and affordable inflammatory markers tested on admission may be useful as predictors of in-hospital mortality in COVID-19 patients requiring hospitalization.